Local properties of Fourier series - Hüseyin Bor (International Journal of Mathematics and Mathematical Sciences)
A theorem on local property of |N¯,pn|k summability of factored Fourier series, which generalizes some known results, and also a general theorem concerning the |N¯,pn|k summability factors of Fourier series have been proved.